Checklist-Based Inspection Technique for Feature Models Review - Mello, Rafael M. de; Teixeira, Eldanae N.; Schots, Marcelo; Werner, Cláudia M. L.; Travassos, Guilherme Horta (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2012: Anais do VI Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2012)
Software Product Line Engineering aims to ensure the correctness, completeness and consistency among its artifacts and the specified domain, in order to prevent the spread of defects for the products derived from this domain. Among initial artifacts of a software product line, feature models are artifacts generated in various domain engineering approaches. Although software inspection is highlighted as an effective review activity for detection of defects in software artifacts, mainly in the early models of software projects, a recent quasi-systematic review of literature indicated a lack of techniques to support the inspection of software product line artifacts, which include features models. Thus, this paper presents FMCheck, a checklist-based inspection technique to support the detection of defects on feature models. This technique was developed to be configurable and to be applied on several extensions of the original feature model notation presented by FODA approach, including the Odyssey-FEX notation, in particular. FMCheck was submitted to a proof of concept and to a further in vitro feasibility study, in which it could be seen the feasibility of FMCheck application and also that inspections applying FMCheck are more effective than ad-hoc inspections, when applied on four distinct domains.